Peace Education of the Sarung-Wearing Community: NU Kyai’s Efforts in Managing Interfaith Diversity through Alternative Education - Herawati, Erna; Fauzi , Soni; Hikmah, Nurul; Ningtiyas, Ratih Kusuma (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
This article analyzes the pivotal role played by Nahdlatul Ulama (NU), an Islamic organization in Indonesia, in embracing religious and cultural diversity through alternative education. The study focuses on the efforts of NU kyais (religious leaders) in the Kasembon House of Worship, Malang, in fostering harmony among religious communities and creating a peaceful environment through education. Adopting a specific approach, this peace education not only concentrates on academic learning but also character formation rooted in humanitarian values, tolerance, and respect for religious differences. This article utilizes a descriptive-analytical approach to explore the peaceful education strategies implemented by NU kyais. Through interviews, observations, and document analysis, this research identifies concrete steps taken by kyais to shape inclusive perspectives and a deeper understanding of religious values and human universality. The findings reveal that the alternative education conducted by NU kyais has successfully created a space for interfaith dialogue, promoted understanding, and built cross-faith cooperation.